Resection of chronic expanding hematoma within the liver cyst difficult to differentiate from liver cystadenocarcinoma: A case report - Kodai Abe; Shunsuke Tomita; Shohei Suzuki; Yu Kigasawa; Hironobu Kashiwagi; Michihito Nishioka; Yasuo Kabeshima (Clinical Case Reports, 2023)
Key Clinical Message Liver cysts are common benign lesions with rare malignancy potential. Distinguishing between benign and malignant tumors within liver cysts is challenging. We present the case of a patient with a chronically expanding hematoma within a liver cyst that was resected under suspicion of liver cystadenocarcinoma. A 73‐year‐old female patient presented with elevated hepatobiliary enzyme levels, no viral hepatitis, elevated tumor marker levels, and preserved liver capacity (Child–Pugh grade A). Abdominal ultrasonography revealed a large cyst (>10 cm) occupying the right lobe and a 25‐mm mass lesion with mixed echogenicity inside the cyst. Contrast‐enhanced computed tomography showed atrophy of the parenchyma of the right lobe and dilation of the right intrahepatic bile duct due to the large cyst. Moreover, in the arterial phase, a point‐like high‐density area was observed inside the nodule, which increased from 25 to 35 mm over 3 months. Diffusion‐weighted magnetic resonance imaging revealed a high‐intensity signal within the nodule; however, positron emission tomography did not show an increased accumulation of fluorodeoxyglucose in the same area. Considering the risk of peritoneal dissemination if the cyst was punctured and found to be malignant, we performed a right hepatectomy. Pathological findings revealed a brownish fluid‐filled cyst containing a dark reddish nodule diffusely filled with hematoma, confirming the absence of a malignancy. To date, the patient has not experienced recurrence. We encountered a case of a chronic, expanding hematoma originating from a liver cyst that was difficult to distinguish preoperatively from a liver cystadenocarcinoma.